THE EFFECT OF PLASTIC PRICE INCREASES ON PRODUCTION COSTS AND SMES PROFITABILITY: EVIDENCE FROM A GREEN ACCOUNTING PERSPECTIVE - Siti Sharah; Nurunnisa Nuzulurrahmah; Irfan S. Himawan; Elan Eriswanto (International Journal of Accounting Innovation, 2026)
Objective: This study aims to analyze the impact of rising plastic prices on production costs and profits of SMEs and examine the role of green accounting as a strategy in addressing cost pressures and sustainability demands. Method: The study used a qualitative approach with a literature review method sourced from scientific journals, articles, and trusted publications. Results: The results show that a significant increase in global oil prices in 2026 will have a direct impact on the price of plastic raw materials, a petrochemical derivative. A 40%–100% increase in plastic prices will increase the Cost of Goods Sold (COGS) and reduce SMEs profits by around 50%. This condition creates economic pressure that increases SMEs' vulnerability to fluctuations in global raw material prices. In facing these conditions, SMEs implement various adaptation strategies through innovation, such as efficient use of raw materials, waste reduction, and the application of the circular economy concept. Novelty: Furthermore, the implementation of green accounting is a strategic solution in identifying and managing environmental costs more effectively. Green accounting not only improves cost efficiency but also strengthens financial resilience and supports business sustainability. However, its implementation in SMEs still faces limitations in terms of understanding and resources. Therefore, support from various parties is needed to encourage the wider adoption of green accounting.